The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1088/0031-9155/60/17/6865
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric accuracy of a treatment planning system for actively scanned proton beams and small target volumes: Monte Carlo and experimental validation

Abstract: This study was performed to evaluate the accuracy of a commercial treatment planning system (TPS), in optimising proton pencil beam dose distributions for small targets of different sizes (5-30 mm side) located at increasing depths in water. The TPS analytical algorithm was benchmarked against experimental data and the FLUKA Monte Carlo (MC) code, previously validated for the selected beam-line. We tested the Siemens syngo(®) TPS plan optimisation module for water cubes fixing the configurable parameters at cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…These results show that beyond the accurate transport of particles in the target, the initial conditions of the beam are also fundamental. This observation is consistent with the results of Magro et al ( 11 ) between the same TPS and MC simulations for small targets at shallow depths. Beamline approximations used for MC simulations are giving, in general, good results, as shown in Bauer et al ( 8 ) for the MC framework, where the differences between simulations and measurements are in average below 3%, or in Grassberger et al ( 12 ) where their model compared to a full beamline propagation show differences inferior to 1% in the middle of a SOBP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results show that beyond the accurate transport of particles in the target, the initial conditions of the beam are also fundamental. This observation is consistent with the results of Magro et al ( 11 ) between the same TPS and MC simulations for small targets at shallow depths. Beamline approximations used for MC simulations are giving, in general, good results, as shown in Bauer et al ( 8 ) for the MC framework, where the differences between simulations and measurements are in average below 3%, or in Grassberger et al ( 12 ) where their model compared to a full beamline propagation show differences inferior to 1% in the middle of a SOBP.…”
Section: Discussionsupporting
confidence: 93%
“…A challenging clinical entity has been selected for testing the PS application: an arterio-venous malformation (AVM) that is a small target inferior to 20 ml in most of the cases and below 3 ml in our study, treated at HIT with protons in one fraction of 18 Gy RBE at the isodose 80%. Magro et al ( 11 ) found for small targets at shallow depth discrepancies between TPS and measurements in water up to ~19%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main benefits of proton therapy is the ability to control the distal range of the treatment field by taking advantage of the Bragg Peak. This allows for the treatment of target volumes located proximal to normal tissue or organs at risk with little dosimetric detriment to the non‐target volumes . When target volumes are located relatively deep in the patient, the accuracy of the TPS is sufficient .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular concern is the dose deposition in highly inhomogeneous patient regions, that is, in the presence of metal implants, thick bones, or cavities. The treatment of small volumes requiring the use of small fields, or the treatment of shallow regions requiring the use of range shifters and large air gaps are also not accurately modeled by commercial TPSs. In these cases, Monte Carlo simulations are a valuable instrument to obtain more reliable dose maps .…”
Section: Introductionmentioning
confidence: 99%